Prevention is Always Better than Cure - Gupta, Sujaya; Dhami, Bhageshwar (Journal of Nepalese Society of Periodontology and Oral Implantology, 2017)
Preventive dentistry is what every dentist and periodontist aims for. A hospital-based study in Nepal showed that staggering 52.5% suffered from gingivitis and 47.5% suffered from periodontitis (28.3% localised, 18% generalised).1 The two major risk factors for various periodontal diseases that can easily be prevented are: tobacco smoking and dental plaque.